Legal Protection for BPJS (Social Security Administrating Body) Participants in Health Services - Alfathan, Andy Reza; Rahman, Abd; Abbas, Ilham (Fakultas Hukum, Universitas Muslim Indonesia, 2025)
This study aims to analyze the legal protection afforded to BPJS Health participants in healthcare services, particularly inpatient services at Andi Makkasau Regional General Hospital, Parepare, by examining the conformity between legal norms and service practices in the field. The research employs an empirical method with a qualitative approach through interviews and literature review of relevant laws and regulations. The findings indicate that the rights and obligations of BPJS Health participants have a strong legal basis, primarily grounded in the National Social Security System Act and BPJS Health Regulation Number 1 of 2014, and have generally been implemented in accordance with applicable provisions, including services based on treatment class, medical indications, and the guarantee of emergency services without additional charges. Existing problems faced by BPJS participants include limited facilities, complex administrative procedures, and low levels of participant understanding of the tiered service mechanism, which give rise to perceptions of unequal treatment. This study concludes that legal protection for BPJS Health participants must continue to be strengthened through improvements in service quality, administrative simplification, and enhanced education and supervision to ensure that the fulfillment of the right to health services can be realized in a fair and dignified manner